Cloud-Based Financial Reporting System Design for Micro Enterprises in Indonesia - Erin, Erin (LPPM Universitas Islam 45 Bekasi, 2024)
The use of information systems has increasingly developed, especially in business. However, micro enterprises in Indonesia still use minimal information systems, especially Accounting Information Systems (AIS) to create financial reports. In fact, using AIS is very important to record all transactions that occur and helps in producing good financial reports. The need for high capital costs and limited knowledge are obstacles to using AIS. Therefore, this research aims to produce a design for building AIS to be able to produce cloud-based financial reports so that micro enterprises can utilize the services provided by the cloud so that they do not need to have capital costs and focus more on business rather than focusing on IT infrastructure to build system. This research was carried out using a qualitative approach with data collection methods using observation using literature studies and system design methods using the Rational Unified Process (RUP) method which was limited to making prototypes. The results of this research are system designs in the form of system architecture and system prototypes